Explaining the spatial segregation of ethnic groups in an early industrial city: the case of Vyborg. - Härkönen, Antti (Digital Scholarship in the Humanities, 2024)
An early industrial town's spatial segregation is studied using empirical data concerning the Russian population of the town of Vyborg. Several hypotheses for explaining segregation are considered using spatial analysis. The spatial data are derived from historical maps and demographic data from various tax records. Socioeconomic segregation is studied as a possible cause of ethnic segregation. The main drivers of spatial segregation were the explicit policies of segregation enforced by both the Russian military administration and the town's civilian administration. While the effects of segregation gradually diminished due to social diffusion, the impact of policy decisions driving segregation in the 18th and early 19th centuries was still visible in the population's later 19th-century segregation. Yet neither the different preferences of Russians and others nor the income differences between areas explains the distribution of Russians. Segregation based on the membership of a guild was insignificant, with a few exceptions. Other factors such as discrimination, prejudice, and differences in housing market information probably contributed to segregation, but they cannot be studied with the data used.